2016
DOI: 10.1016/j.jbi.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling assistive technology adoption for people with dementia

Abstract: We conclude that modelling user adoption from a range of parameters such as physical, environmental and social perspectives is beneficial in recommending a technology to a particular user based on their profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Considering the research constraints, it is concluded that the use of an assistive technology-based educational model has been effective in increasing academic satisfaction among individuals with physical mobility impairments. In sum, the results of this finding were well-matched with those of done by researchers such as Velayati, 17 Allahi et al, 18 Jangizehi Shastan et al, 19 and with those of conducted by foreign scholars such as Simoes et al, 12 Lee et al, 32 Lan and Sie, 33 Kuo et al, 34 Abdallah and Fayyoumi, 22 Hussein et al, 20 Kim et al, 27 Vereenooghe et al, 25 Chaurasia et al, 23 Lersilp et al, 26 and Toofaninejad et al 24 In explaining this finding, it can be argued that assistive technologies enable individuals with physical mobility impairments to enjoy all kinds of tools, and help them to practice and improve their academic and social skills. 35 Only a few technology applications exist that can be used for entertainment and education; for example, computeraided instructional programs, assistive technology tools, virtual environments, video modeling, mobile technologies (iPad systems, touch pads, or iPhones) and computer games.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Considering the research constraints, it is concluded that the use of an assistive technology-based educational model has been effective in increasing academic satisfaction among individuals with physical mobility impairments. In sum, the results of this finding were well-matched with those of done by researchers such as Velayati, 17 Allahi et al, 18 Jangizehi Shastan et al, 19 and with those of conducted by foreign scholars such as Simoes et al, 12 Lee et al, 32 Lan and Sie, 33 Kuo et al, 34 Abdallah and Fayyoumi, 22 Hussein et al, 20 Kim et al, 27 Vereenooghe et al, 25 Chaurasia et al, 23 Lersilp et al, 26 and Toofaninejad et al 24 In explaining this finding, it can be argued that assistive technologies enable individuals with physical mobility impairments to enjoy all kinds of tools, and help them to practice and improve their academic and social skills. 35 Only a few technology applications exist that can be used for entertainment and education; for example, computeraided instructional programs, assistive technology tools, virtual environments, video modeling, mobile technologies (iPad systems, touch pads, or iPhones) and computer games.…”
Section: Discussionsupporting
confidence: 87%
“…[14][15][16] Numerous studies have all pointed out in their research that assistive technology such as mobile, multimedia and virtual social networks can play an important role in teaching individuals with special needs such as physical mobility, hearing, or visual impairments, or individuals with mental retardation. [17][18][19][20][21][22][23][24][25][26][27] However, in the country of Iran, no activities to facilitate the learning of individual with physical mobility impairments using assistive and targeted technology have been reported. As noted above, there is interest in and use and integration of technology in various curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Domain‐specific models for prediction have also been proposed. Chaurasia et al () present Technology Adoption and Usage Tool that focuses on modelling adoption of assistive technology by PwD and their carers. The model was built upon a diverse dataset obtained by recruiting 335 participants from the Cache County Study on Memory in Aging and linking this database to the Utah Population Database.…”
Section: Primary Studies From the Literaturementioning
confidence: 99%
“…When examining adoption and acceptance of assistive technologies, researchers often profile users based on their engagement or lack thereof with the technology [14,15]. This results in a matrix of adoption, describing whether the person will use the technology, based on two factors: whether the technology is usable by the participant and whether they see a perceived utility in the solution.…”
Section: Determinants Of Technology Adoptionmentioning
confidence: 99%
“…Regression-based models have demonstrated the ability to identify, with high levels of precision, individuals who are likely to adopt technology-based solutions [15]. Input parameters to these models have ranged from details relating to education, living arrangements, prior technology experience, and medical history [15].…”
Section: Pillar 3: Adoption Modelingmentioning
confidence: 99%